Presbicia y su incidencia en el rendimiento laboral de los docentes de la unidad educativa "Abdón Calderón" parroquia Barreiro de la ciudad de Babahoyo primer semestre del 2022. - León Del Barco, Kevin Ronaldo (2022)
This present study has as its principle and purpose to know presbyopia and its impact on the work performance of teachers of the Educational Unit "Abdon Calderon" belonging to the Barreiro parish of the city of Babahoyo, presbyopia is a visual problem that occurs to 40 years onwards in everyone in a natural way. The problem in teachers is that when this is not treated it will influence their work and social performance, it is important that people who suffer from a visual problem go to a professional of the visual health to be able to detect the origin that causes them and these are corrected and prevent these visual problems from worsening over time or harming them professionally. This project helped us to set objectives around the problem, which was chosen through optometric procedures. For the completion of this investigation we deliver brochures where we give all the necessary information so that teachers are informed about the importance of knowing what presbyopia is about, how it will affect their work and environment, the treatments they have to do to improve your life and how important it is to go to a professional in the area.